2021
DOI: 10.3389/fneur.2021.574649
|View full text |Cite
|
Sign up to set email alerts
|

Snoring Is Associated With Increased Risk of Stroke: A Cumulative Meta-Analysis

Abstract: Background: Several studies have suggested that snoring is associated with an increased risk of stroke; however, the results are inconsistent. We aim to conduct a systematic review and meta-analysis of observational studies assessing the association between snoring and the risk of stroke in adults.Methods: We searched PubMed for relevant studies. A random-effect model was adopted to summary relative risks (RRs), and forest plots from a cumulative meta-analysis method were used for a better presentation of how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Snoring could cause anoxemia, leading to oxidative stress responses and endothelial dysfunction, 41 all of which might lead to atherosclerosis and contribute to incident stroke. 42 In addition, a high-level vibration transmitted to the carotid artery caused by snoring might trigger a cascade effect on the numerous cells of the arterial wall and lead to injury to the vessel and rupture of plaque. 42 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Snoring could cause anoxemia, leading to oxidative stress responses and endothelial dysfunction, 41 all of which might lead to atherosclerosis and contribute to incident stroke. 42 In addition, a high-level vibration transmitted to the carotid artery caused by snoring might trigger a cascade effect on the numerous cells of the arterial wall and lead to injury to the vessel and rupture of plaque. 42 …”
Section: Discussionmentioning
confidence: 99%
“… 42 In addition, a high-level vibration transmitted to the carotid artery caused by snoring might trigger a cascade effect on the numerous cells of the arterial wall and lead to injury to the vessel and rupture of plaque. 42 …”
Section: Discussionmentioning
confidence: 99%
“…There is convincing evidence that sleep apnea is related to obesity, T2D, and HTN etiology [ 1 , 30 , 33 ]. Further, snoring has been linked to poorer cardiovascular health and higher cardiometabolic risk scores that encompass BMI, BP, and fasting glucose [ 34 , 35 ], and in a meta-analysis to 46% higher risk of incident stroke [ 36 ]. Difficulty falling asleep (an insomnia complaint) was also consistently related to all study outcomes and has been extensively linked to cardiometabolic risk factors [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these findings about the association between stroke risk and snoring could not be verified whether habitual snoring was associated with stroke risk and required further research. Recently, a result of a meta-analysis including 3,598 stroke patients and 145,901 participants without stroke, suggested that snoring was associated with a significantly increased risk of stroke (relative risk 1.46; 95% CI, 1.29–1.63; P < 0.001) ( 31 ). A similar meta-analysis conducted by Min Li et al reported that snoring had a modest but statistically significant positive association with the risk of stroke ( 32 ).…”
Section: Discussionmentioning
confidence: 99%